ChemInform Abstract: Ba2TeO: A New Layered Oxytelluride. Issue 9 (March 2015) - Besara, T.; Ramirez, D.; Sun, J.; Whalen, J. B.; Tokumoto, T. D.; McGill, S. A.; Singh, D. J.; Siegrist, T.
Abstract Single crystals of the semiconducting Ba2TeO are prepared from BaO and Te in a molten Ba flux in the molar ratio of 1:1:20 (steel crucible in evacuated quartz tube, 1000 °C, 20 h; cooling to 820 °C within 50 h).